Study of hemodynamic and airway reflexes during emergence from general anaesthesia and tracheal extubation with and without using dexmedetomidine in patients undergoing laparoscopic cholecystectomy - KC, Gaurav; Amatya, Bishwo Ram; Bista, Sachhyatkar (Journal of Patan Academy of Health Sciences, 2024)
Introduction: The emergence phase and tracheal extubation are critical due to potential hemodynamic changes and airway reflexes. This study aimed to evaluate the effectiveness of Dexmedetomidine in mitigating these responses during extubation. Method: Forty-eight American Society of Anesthesiologists physical status (ASA-PS) I and II patients, aged 18-60 years , undergoing elective laparoscopic cholecystectomy were enrolled at Shree Birendra Hospital, Kathmandu after Institutional Review Committee approval. Group D received 0.25 mcg/kg Dexmedetomidine in 100 ml saline, while Group N received 100 ml saline over 10 minutes at the end of surgery. Heart rate and Mean Arterial Pressure (MAP) were recorded at different time intervals. Extubation smoothness was rated on a 5-point scale. Statistical analysis used Fisher’s exact test/chi-square test for categorical variables and Mann-Whitney test or independent t-test for continuous variables. Repeated measures were assessed with RM ANOVA. A p-value of <0.05 was considered significant. Result: Demographic profiles and ASA-PS statuses were similar between groups. Group D had a lower Heart rate compared to Group N at 10 minutes post-administration and showed more stable Heart rate changes around extubation. Significant differences in Heart rate were observed at 10 minutes post-administration, during extubation, and at 1, 3, 5, and 10 minutes post-extubation. Group N had higher MAP levels during and after extubation. Extubation smoothness was better in Group D, with 54.17% achieving a score of 1 versus 4.17% in Group N. Conclusion: Pre-emptive Dexmedetomidine effectively reduces hemodynamic reflexes and facilitates smoother extubation.